Succession, Not Possession Sarah’s Inheritance in Tobit - Vos, Daniel J. (2025)
Analyses of the marriage of Tobiah and Sarah in the Book of Tobit have frequently appealed to biblical descriptions of levirate marriage to explain Tob 3:7 and 6:12, in which Tobiah is said to have the right to "inherit her." Through a closer reading of the text in light of Abraham’s complaint about the lack of an heir in Gen 15:3-4 and the Jewish Aramaic legal tradition, I argue that these verses refer to succession to Reuel’s estate through marriage to Sarah. Tobiah does not inherit Sarah, but inherits through marriage to Sarah.
Keywords: Tobit; Biblical Law; Inheritance; Marriage